Comparing one-year outcomes of invasive versus medical management of patients with prior coronary artery bypass graft surgery presenting with non-ST elevation myocardial infarction. (14th October 2021) - Ramtoola, M T; Hartemink, J W; Dhuny, S; Nathan, J; Shabbir, H; Shafiq, A; Garg, S A
Abstract: Background: Early percutaneous coronary intervention (PCI) has a Class 1A recommendation for patients with non-ST elevation myocardial infarction (NSTEMI). However, the benefits of this invasive approach in patients with previous coronary artery bypass graft (CABG) surgery are uncertain, as these patients have previously been excluded from pivotal trials. Purpose: We hypothesised that routine invasive management in patients with previous CABG presenting with NSTEMI, but otherwise medically stable, carried similar prognostic outcomes to patients who were medically managed. Methods: This single centre retrospective observational study screened patients with prior CABG presenting with NSTEMI between January 2015 and December 2019. Patients either underwent coronary angiography with or without PCI at their physician's discretion or received standard acute coronary syndrome (ACS) medical therapy. Follow up time was 365 days from admission date, and clinical, demographic, procedural and outcome data were collected. The primary endpoint was major adverse cardiac events (MACE), a composite of all-cause mortality and rehospitalisation for unstable angina, myocardial infarction, or heart failure. Results: The study included 267 patients (mean ±SD age: 72±10 years, 82% male), of whom 80.1% (N=214) underwent cardiac catheterisation, and 19.9% (N=53) only received standard ACS medical therapy. Amongst the invasive group, 65.4% (N=140) received PCI. No one was referred for re-do CABG. At 1-year follow up, the primary composite outcome occurred in 18 (13%) patients in the PCI group, 13 (18%) in those managed conservatively following angiography, and in 27 (51%) patients receiving medical therapy only. Cox regression modelling showed no significant difference in the 1-year primary endpoint amongst those having an angiogram who received PCI versus those treated medically after invasive assessment (HR: 0.75 [95% CI: 0.38–1.48; P=0.412]). Previous revascularisation with PCI (HR: 1.90 [CI, 1.11–3.24; P=0.018]) and chronic kidney disease (CKD) (HR: 2.60 [CI, 1.56–4.34; P<0.001]) at any stage, were the most important predictors of poor outcomes in CABG patients with NSTEMI irrespective of management strategy. Conclusion: Patients with previous CABG who are admitted with NSTEMI who were not considered suitable for invasive angiography experienced significantly higher rates of MACE at 1-year follow up. The presence of CKD or previous PCI were key indicators of poor outcomes irrespective of management strategy. Outcomes amongst those deemed fit enough for invasive angiography were similar irrespective of treatment, suggesting that additional non-invasive testing may help further define which patients would benefit from an invasive strategy. Funding Acknowledgement: Type of funding sources: None.